Power Quality Mitigation Technologies in a Distributed Environment - Moreno-Muñoz, Antonio (Power Systems, 2007)
With the generalized use of personal computers, microelectronic-based instrumentation and other susceptible devices, the subject of power quality and its relationship to the vulnerability of high-tech facilities is becoming an increasing concern, not only to the utility companies but also to the end-customer. In the 21st century, instrumentation and control operations require high quality and ultra-reliable power in quantities and time frames never experienced before. Power Quality: Mitigation Technologies in a Distributed Environment presents a solid theoretical foundation of the modern mitigation technologies employed in the power quality arena, and provides an overview of the most recent challenges in this field. Readers will learn about: how to deal with the multifaceted characteristics of power quality studies; how circuit and process design can be affected by the most common power disturbances; the implications that electromagnetic compatibility has on the equipment and installation design; how power electronic devices can improve the power quality of the distribution supply; and, the advances in IT that can support a better power quality. Power Quality: Mitigation Technologies in a Distributed Environment introduces the advanced concepts associated with power quality to engineers and students. It will make an excellent reference for facility electrical power engineers and maintenance technicians.